Three-dimensional airways volumetric analysis before and after fast and early mandibular osteodistraction. Issue 3 (March 2017) - Ramieri, Valerio; Basile, Emanuela; Bosco, Giulio; Caresta, Elena; Papoff, Paola; Cascone, Piero
Abstract: Purpose: Newborns with Pierre Robin sequence (PRS) and syndromic micrognathia show microgenia and glossoptosis, which cause reduction of the airway and breathing difficulty from birth. Our goal is to analyze quantitative and qualitative volumetric changes before and after fast and early mandibular osteodistraction (FEMOD) and to compare radiological data. Methods: The sample was composed of 4 patients, who satisfied inclusion criteria for completeness of data. Computed tomography pre- and post-operation were performed, then a volumetric assessment was made with Dolphin Imaging. Polysomnography was performed before and after FEMOD. Results: Pre- and post-operative CT scan data were compared. The analysis of all three sections showed a significant increase of volumetric parameters. The retroglossal volume average increase was 346%, and the retropalatal volume average increase was 169%. These data matched the improvement recorded by polysomnography. Conclusions: The data confirm FEMOD as an efficient treatment to improve airways and breathing problem in patients affected by Pierre Robin sequence and syndromic micrognathia. The three-dimensional volume rendering could be a useful method to evaluate and quantify the increase in airways volume.